Retinal detachment following excimer laser. Issue 9 (1st September 1997) - Charteris, D G; Cooling, R J; Lavin, M J; McLeod, D
Abstract : AIMS: To report the clinical presentation, surgical management, and outcome of retinal detachment following excimer laser. METHODS: Retrospective analysis of retinal detachments observed in 11 eyes of 10 myopic patients who had previously undergone photorefractive keratectomy (PRK) or phototherapeutic keratectomy (PTK) by excimer laser. RESULTS: Symptoms of visual loss in two eyes were initially attributed to corneal haze. In 10 of 11 eyes visualisation of the retinal detachment and causative break was possible despite mild corneal haze and optical aberrations caused by the refractive laser procedure. Retinal reattachment was achieved in all 11 eyes though one eye required four surgical interventions. CONCLUSION: This is the first published report to describe an association between retinal detachment and previous excimer laser treatment. The association would appear to reflect the predisposition of myopes to retinal detachment. Clinicians should be aware of potential retinal pathology in patients undergoing PRK.